Redesign business model options for "University of the Future" and staying relevant in the fourth industrial revolution age - Ahmad Dahlan, Abdul Rahman; Ibrahim, Jamaludin; Mohamed Jalaldeen, Mohamed Razi; El Mohajir, Mohammed (Kulliyyah of Information and Communcation Technology, International Islamic University Malaysia, 2020)
Several key studies have shown that the higher education sector is in need of new business models in order to stay relevant and sustainable in the New Digital Age. Pressures and drivers of change – funding, changes in the technology and Fourth Industrial Revolution (4IR), digital socio-economy, and business model, to name a few – that demand institutional change by re-examine its existing business model and value proposition, if success is to be sustained over the long term. The digital changes are dynamic and complex. This paper adopted the design and system thinking approach. Strategy canvas with business modeling tools such as the Environmental Map (EM), Business Model Canvas (BMC) and Value Proposition Design Canvas (VPC) are modeling tools used to design, evaluate alternative business models and value propositions. The tools allows us to design business model options that create value for the business, and value propositions that create value for the customers, thus enabling the creation of sustainable businesses. In this paper we explore the use of business modeling tool to analyse, formulate, and design sustainable business models for the University of the Future (UotF) in facing the New Digital Age challenges and opportunities. Depending on the value proposition offered to targeted customer segments, this paper has established generic business model prototypes for UotF in the facing the challenges and opportunities created by the New Digital Age and 4IR. In our opinion these generic prototype options will help university decision makers, planners and relevant stakeholders to continuously enhance and customise sustainable, agile, and competitive business models.